Growth or equity? Reflections on some recent tendencies in the agricultural policy of LDCs - Rolf Hanisch (Intereconomics, 1976)
The following article deals with the aims and consequences of the use of large (urban) enterprises in food production within the compass of agricultural development strategies.
Keywords: 330; Agricultural Policy